2022
DOI: 10.1186/s12920-022-01366-x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic liability to obesity and peptic ulcer disease: a Mendelian randomization study

Abstract: Background Epidemiological evidence relating obesity to peptic ulcer disease (PUD) has been mixed. Here we sought to determine the causality in the association of obesity with PUD risk using the Mendelian randomization (MR) approach. Methods This study was based on summary-level data for body mass index (BMI), waist-to-hip ratio (WHR), and PUD derived from large genome-wide association studies (GWASs). Single nucleotide polymorphisms significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…In our study, we carried out a Mendelian randomization study of the three diseases most likely to be induced by H. pylori with T2DM, and the results showed that gastric cancer was not causally related to T2DM, while gastroduodenal ulcer and chronic gastritis were associated with the development of T2DM, and in order to further explore the mechanism of the occurrence of this causality, we compared the two diseases with the T2DM development, respectively. Mendelian analysis of obesity, HbA1c and blood glucose levels, respectively, which showed that gastroduodenal ulcer was a risk factor for increased risk of obesity, so we hypothesized that obesity might be a mediator between gastroduodenal ulcer and T2DM, and then we carried out the validation, and the result was in line with our speculation that gastroduodenal ulcer mediated T2DM through obesity, which was in line with the results of previous results of a Mendelian study on the association between peptic ulcer and obesity [38], therefore, obese patients with gastroduodenal ulcer should be carefully managed to prevent T2DM.…”
Section: Plos Onesupporting
confidence: 86%
“…In our study, we carried out a Mendelian randomization study of the three diseases most likely to be induced by H. pylori with T2DM, and the results showed that gastric cancer was not causally related to T2DM, while gastroduodenal ulcer and chronic gastritis were associated with the development of T2DM, and in order to further explore the mechanism of the occurrence of this causality, we compared the two diseases with the T2DM development, respectively. Mendelian analysis of obesity, HbA1c and blood glucose levels, respectively, which showed that gastroduodenal ulcer was a risk factor for increased risk of obesity, so we hypothesized that obesity might be a mediator between gastroduodenal ulcer and T2DM, and then we carried out the validation, and the result was in line with our speculation that gastroduodenal ulcer mediated T2DM through obesity, which was in line with the results of previous results of a Mendelian study on the association between peptic ulcer and obesity [38], therefore, obese patients with gastroduodenal ulcer should be carefully managed to prevent T2DM.…”
Section: Plos Onesupporting
confidence: 86%
“…It is reported that obesity, smoking, anticoagulant, and other risk factors are often related to gastrointestinal diseases ( 39 41 ). The GWAS of GERD and PUD found genetic overlapping with the identified aforementioned hazardous factors ( 42 , 43 ). We cannot rule out that SNP affects the outcome through other related variables.…”
Section: Discussionmentioning
confidence: 99%
“…Mendelian randomisation (MR) is an instrumental variable (IV) analysis that detects and quantifies causality using genetic variation as an IV [ 23 ]. Because of its ability to overcome potential confounding factors and reverse causality, MR has been increasingly used in observational studies in recent years [ 24 26 ]. Therefore, this study aimed to clarify the causal association between PCOS, its characteristics, and OS using a two-sample MR study.…”
Section: Introductionmentioning
confidence: 99%